Enhanced Fluid Mixing in Microchannels Using Levitated Magnetic Microrobots: A Numerical Study - Ali Anil Demircali; Abdurrahim Yilmaz; Huseyin Uvet (Micromachines)
The efficient mixing of fluids at microscale dimensions presents challenges due to the dominant laminar flow regime which restricts convective mixing. This study introduces a numerical analysis of a novel microrobotic mixing system with a levitated propeller robot, driven by magnetic fields, within a Y-shaped microchannel with a square cross-section (500 × 500 μm). Our research investigates the fluid mixing effectiveness facilitated by the microrobot through various levitation heights and orientations to enhance the mixing index (MI). This index is tested under different conditions by leveraging the dynamics of the propeller robot, characterized by adjustable roll and pitch angles and varying levitation heights. The numerical simulations, conducted using COMSOL® (Finite Element Method, FEM) software, integrate Maxwell’s equations for magnetic field interaction with momentum and transport-diffusion equations to analyze fluid dynamics within the microchannel. Results indicate that the propeller robot can achieve an MI of up to 98.94% at a 150 μm levitation height and 1500 rpm propeller speed within 3 s. Additionally, the study examines the impact of propeller speed, Reynolds number, and robot length on mixing performance, providing comprehensive guidance for optimizing microscale fluid mixing in lab-on-a-chip applications.